2010
DOI: 10.1007/s11738-010-0587-6
|View full text |Cite
|
Sign up to set email alerts
|

Light restored root growth of Arabidopsis with constitutive ethylene response

Abstract: Ethylene response factor (ERF) is an important component in ethylene or pathogen-induced defensive response of plants. However, physiological effects of ERF on plants have not been fully elucidated. We previously identified an ERF gene, OsERF1, in rice. It up-regulated ethylene-responsive genes expression and influenced growth and development of the transgenic Arabidopsis. Here, we report that similar to other seedlings with constitutive ethylene response, OsERF1 seedlings were suppressed in their root growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…The glycine-induced phenotype in our work is consistent with the results observed in ethylene studies: cell elongation inhibition, stimulation in radial expansion, and root hair elongation (Hu et al, 2011;Leblanc et al, 2008;Strader et al, 2010). It is known that ethylene controls root cell expansion through auxin (Strader et al, 2010) by inhibiting plasma membrane H + -ATPase activity (Staal et al, 2011).…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…The glycine-induced phenotype in our work is consistent with the results observed in ethylene studies: cell elongation inhibition, stimulation in radial expansion, and root hair elongation (Hu et al, 2011;Leblanc et al, 2008;Strader et al, 2010). It is known that ethylene controls root cell expansion through auxin (Strader et al, 2010) by inhibiting plasma membrane H + -ATPase activity (Staal et al, 2011).…”
Section: Methodssupporting
confidence: 90%
“…pH and light conditions play an important role in the plant response to signals (Brenner et al, 2000;Hu et al, 2011;Thornton, 2001). The habanero pepper is typically grown in soil at pH 7.5 in the Yucatán (Borges-Gómez et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, ethylene stimulates auxin biosynthesis and basipetal auxin transport toward the root elongation zone, where it activates a local auxin response, leading to inhibition of cell elongation [15,17]. A recent study reported that light restores the suppressed root growth of OsERF1 transgenic Arabidopsis plants showing constitutive ethylene response [38]. However, our results indicated that the inhibition on root growth of GhERF12 transgenic plants seems to be not restorable by light irradiation (Figure 4), suggesting that the role of GhERF12 in ethylene response may be slightly deferent from that of OsERF1.…”
Section: Discussionmentioning
confidence: 99%
“…OsRMC , a plasma membrane protein of DUF26 signal peptide, participates in JA signal transduction, mediates rice root development, and negatively regulates root curling [ 24 ]. Ethylene can promote auxin synthesis and regulate plant root cell elongation [ 25 , 26 ]. However, it remains unclear whether ethylene regulates root development through auxin accumulation and transport in rice.…”
Section: Introductionmentioning
confidence: 99%